ANTRIAN KONSUMEN PADA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU ) NO. 64 – 75364 JLN. YOS SUDARSO II SANGATTA - Herli, Awang (EKONOMIA, 2013)
The purpose is to analyze the service activity to customer (veticle ) on public on station  No. 64-75364 At Yos sudarso II street Sangatta. Research was conducted for 3 months ( April to Juni 2013 ) On public Gas Station Sangatta, related to costomer queue  at public gas station No. 64 – 75364 on Yos Sudarso II srett Sangatta. Research activities are includes : Literature study, field observation, interviews, documentation, data collection and analysis. Data collected are indude : Public gas station general description, organizational structure, and respondent answers. Data analisis used Analize tool 1) Potential use calculation 2) Average queue calculation 3) Queue long  4) Average veticles number in queue.Based on calculation shows that diesel Gas filling is for 1,08 second Premium gasoline. Is for 34 second. Average customer number in queue according to  research are diesel gas filling 0,0003 customer per minute, Premium gasoline filling 0,1184 cutomer per minute. Meanwhile the probability of none waiting system of premium gasoline filling is 0,4347 and the probability of none waiting system of diesel gasfilling is 0,3333. Resuly of service level premium gasoline and diesel gas each for single line and single facility obtained  80%  means there is 20% ree time. and for the fuel filling with single line and double facility obtained each 40% means there is 60% free time.